Afiks Pembentuk Verba dalam Bahasa Mentawai di Desa Sirilogui Kecamatan Siberut Utara Kabupaten Kepulauan Mentawai - Maria Adriana; Ngusman Abdul Manaf (Persona: Kajian Bahasa dan Sastra, 2022)
Derived verbs in the Mentawai language are also formed from morphological processes, one of which is affixation. Affixes in the Mentawai language have several forms that sometimes make one mistaken for attaching affixes to basic words in an utterance. This study describes the types and meanings of verb-forming affixes in the Mentawai language in Sirilogui Village, North Siberut District, Mentawai Islands Regency. This research is a qualitative research using descriptive method. The research data is in the form of affixed verbs with the data source being Mentawai language speech in Sirilogui Village, North Siberut District, Mentawai Islands Regency. The data in this study were collected using two methods, namely the listening method with tapping techniques and the speaking method with interview techniques. Data analysis was carried out by transcribing the data into written language, grouping the data into the format provided, analyzing technically for direct elements, and identifying meaning using referential techniques. From the results of the analysis found 74 verbs with affixes in three types of affixation, namely (1) prefixes consisting of prefixes atu-, mu-, pasi-, si-, (2) -aken suffixes, and (3) combinations of pasi- and - affixes. account. The meaning of verb-forming affixes in this study is the grammatical meaning which states 'in a state', 'already happened', 'issuing or producing', 'doing activities', doing (basic)', 'doing work with tools', 'doing (basic)', 'do will', 'make it' and 'do it for someone else'